PERFORMANCE OF WARM MIX ASPHALT BINDER COURSE (AC-BC) USING ECONUSKA MODIFIED ASPHALT - JANNATUN NISSA, ANITA
Generally, warmix asphalt technology is aimed to improve the energy efficient by lowering the mixing and compaction temperatures without reducing the final quality of the asphalt mixture. Warmix asphalt researches in Indonesia has been conducted using a variety of additive products including natural zeolite and Leadcap. The latest development was undertaken in collaboration between Institute of Road Engineering (Indonesia) and the Korean Institute of Construction Technology (South Korea) in developing a warm mix asphalt technology for heavy traffic volume under a name of Econuska. The objective of this study is to evaluate the laboratory performance of warmix asphalt using Econuska modified asphalt. The first stage of the asphalt testing is using DSR for Eckonuska binder and also pen 60/70 binder and Starbit polymer modified asphalt as comparison. DSR testing serves as asphalt rheology and performance grade determination, and also to discover the critical temperature of the binder. The mixing and compaction temperature of Econuska were 141 °C and 126 °C respectively, which is 11.3% lower than pen 60/70 and 24.1% lower than Starbit polymer modified asphalt. Furthermore, the mixture performance were obtained through Marshall and Marshall Immersion test as well as Dynamic Stability and Dynamic Modulus test. Dynamic Modulus can also be used to develop the master curve of asphalt mixture. The asphalt mixture master curve provides a relationship between the asphalt mixture modulus and reduced frequency over a range of temperature, so that the viscoelastic properties of the mixture can be predicted. Econuska is able to improve the fatigue resistance dan rutting resistance compared to pen 60/70 binder. In addition, the Dynamic Modulus of Econuska is higher at low temperatures and medium temperatures compared to Starbit polymer asphalt and Pen 60/70 binder.